Review on millimeter wave propagation through sand and dust storm—impact of humidity - Eltahir, E.I.; Islam, Md. Rafiqul; Elsheikh, Elfatih A. A.; Zyoud, Alhareth Mohammed; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Abdul Rahim, Sharul Kamal; Hamdan, Mosab (IEEE, 2025)
In this paper, sand and dust storm characteristics and attenuation prediction methods were reviewed and summarized comprehensively. The impact of humidity on the attenuation prediction process is focally discussed while highlighting the need to incorporate it in the modeling process for accurate attenuation prediction. This review is driven by the need to develop precise prediction models that account for the impact of meteorological factors, particularly humidity, on millimeter-wave attenuation during dust storms. By addressing these shortcomings, the review seeks to improve the design of resilient communication systems to support the ultra-reliable 5G and 6G networks in challenging environments. A critique of the previous studies that highlight the contributions and drawbacks is presented in the paper. This is followed by a taxonomy of models based on their prediction concepts and the timeline of developments. Furthermore, open issues and challenges for research were presented. The review study found that existing theoretical models have failed to predict measured attenuation accurately, often deviating significantly. Most of the theoretical and analytical approaches for estimating dust storm attenuation are found to neglect the critical influence of humidity. Few empirical and machine-learning models proposed recently, have demonstrated closer alignment with measurements after considering humidity and other metrological parameters.